2014
DOI: 10.1182/asheducation-2014.1.306
|View full text |Cite
|
Sign up to set email alerts
|

Central venous catheter–related thrombosis

Abstract: Thrombotic complications associated with the use of central venous catheters (CVCs) are common and lead to distressing patient symptoms, catheter dysfunction, increased risk of infections, long-term central venous stenosis, and considerable costs of care. Risk factors for catheter-related thrombosis include use of larger, multilumen, and peripherally inserted catheters in patients with cancer receiving chemotherapy. Symptomatic catheter-related thrombosis is treated with anticoagulation, generally without remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
141
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(155 citation statements)
references
References 48 publications
3
141
0
11
Order By: Relevance
“…41 CRT can lead to significant discomfort from symptoms, catheter dysfunction, increased risk for infections and long-term risk for venous stenosis. 41 Although CRT clearly contributes to morbidity and catheter dysfunction, the majority of CRT are asymptomatic and there is little evidence that CRT is associated with an increased rate of pulmonary embolism or increased mortality. 42 The primary objectives of treatment of CRT are to reduce symptoms, prevent extension into more central veins, preserve access and to prevent chronic venous stenosis.…”
Section: Catheter-related Thrombosismentioning
confidence: 99%
See 3 more Smart Citations
“…41 CRT can lead to significant discomfort from symptoms, catheter dysfunction, increased risk for infections and long-term risk for venous stenosis. 41 Although CRT clearly contributes to morbidity and catheter dysfunction, the majority of CRT are asymptomatic and there is little evidence that CRT is associated with an increased rate of pulmonary embolism or increased mortality. 42 The primary objectives of treatment of CRT are to reduce symptoms, prevent extension into more central veins, preserve access and to prevent chronic venous stenosis.…”
Section: Catheter-related Thrombosismentioning
confidence: 99%
“…48 Several clinicians prefer to continue anticoagulation for 1-2 weeks after the catheter is removed. 41 …”
Section: Catheter-related Thrombosismentioning
confidence: 99%
See 2 more Smart Citations
“…Although flushing or locking catheters with heparin or saline has been standard practice for years, data demonstrating the effectiveness of these practices is lacking. 28 Anticoagulant thromboprophylaxis to prevent CRT has been the subject of multiple clinical trials (Table 2). [30][31][32][33][34][35][36][37][38][39][40][41][42] Early studies suggested that fixed low-dose warfarin (1 mg/d) or LMWH (dalteparin: 2500 U/d) was associated with reduced rates of CRT in cancer patients.…”
Section: Risk Factors For Crtmentioning
confidence: 99%